Quantitative analysis of water content and distribution in plants using terahertz imaging - Shchepetilnikov, Anton V; Zarezin, Alexey M; Muravev, Viacheslav M; Gusikhin, Pavel A; Kukushkin, Igor V (Optical engineering, 2020)
Quantitative analysis of the temporal evolution and spatial distribution of water content in grass and clover leaves has been carried out in vivo, with the aid of the terahertz imaging system comprised of an impact avalanche and transit time-diode source, a condenser lens, and an imaging camera. The leaf samples were exposed to 100-GHz radiation to measure the transmitted power. Progressive variation in the level of the transmitted signal has been detected when the plants were subject to the condition of insufficient water supply, whereas after watering the plants, the transmission was restored to its initial value. The presented experimental results demonstrate that TeraSense imaging instrumentation can be effectively used to monitor the hydration state of plants in their natural environment.